Transformasi Tata Kelola Investasi Daerah: Studi Kasus Perizinan Berbasis Risiko dan Percepatan Kawasan Industri Terpadu Batang (KITB) di Jawa Tengah - Keisha Nadine Sastraatmaja; Laela Kuwayyis Wijaya; Nasya Nadhira Rahma; Tyazza Amaranila Ghifari (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
The enactment of Law Number 11 of 2020 Job Creation has fundamentally transformed Indonesia’s business licensing system through the implementation of a risk-based business licensing regime, as regulated under Government Regulation Number 5 of 2021. This regulatory shift requires regional governments to realign local regulations and administrative practices to ensure legal certainty, procedural consistency, and effective investment facilitation. Central Java represents a relevant case as a non-mining province that relies heavily on manufacturing industries such as textiles, footwear, automotive, furniture, and electronics as the backbone of regional investment and employment creation. In 2023, Central Java recorded investment realization of IDR 77.02 trillion, exceeding its target and demonstrating strong competitiveness among regions. This study examines the role of Central Java Provincial Regulation Number 12 of 2022 on investment as a legal instrument supporting the transformation of regional investment governance in the post-Job Creation Law era. Using normative legal research with a statute and conceptual approach, this study analyses the harmonization of regional regulations with national investment policies and evaluates their implementation through a case study of the Integrated Industrial Estate of Batang (KITB). The findings indicate that Provincial Regulations No. 12 of 2022 provides a normative foundation for investment facilitation, risk-based licensing, and integrated one-stop services, which contribute to accelerating industrial development in KITB. The study concludes that the integration of regional legal frameworks, risk-based licensing mechanisms, and institutional readiness is essential to maintaining regional investment competitiveness and supporting sustainable industrial growth.